2011
DOI: 10.1111/j.1479-8425.2011.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecstasy and sleep disturbance: Progress towards elucidating a role for the circadian system

Abstract: MDMA (ecstasy) is an illicit drug which has pharmacological actions on the serotonin system, leading to a number of physiological and behavioral changes. Research conducted in both animals and humans has focused on how ecstasy use affects systems or functions in which serotonin has a regulatory role including mood, sleep and circadian rhythms. In this paper we review the evidence with respect to changes in sleep and circadian rhythms following ecstasy use. Studies of the subjective measurement of sleep have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Similar processes may also be at play in the current study. Indeed, disruptions in circadian rhythms have been observed across substance abusing samples (Birchler-Pedross et al, 2009; Ogeil et al, 2012; see Hasler et al, 2012, for review) with continued disruptions observed up to 30 days of abstinence in heroin-using samples for example (Li et al, 2009). Examining the contribution of the circadian system to affect and craving will require the use of specialized protocols capable of parsing out the effects of circadian timing from homeostatic sleep drive in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar processes may also be at play in the current study. Indeed, disruptions in circadian rhythms have been observed across substance abusing samples (Birchler-Pedross et al, 2009; Ogeil et al, 2012; see Hasler et al, 2012, for review) with continued disruptions observed up to 30 days of abstinence in heroin-using samples for example (Li et al, 2009). Examining the contribution of the circadian system to affect and craving will require the use of specialized protocols capable of parsing out the effects of circadian timing from homeostatic sleep drive in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…pharmacokinetics for both alcohol and cannabis results in higher drug concentrations in women following ingestion of the same amount of alcohol and cannabis compared with men; Cooper and Haney, ; Holmila and Raitasalo, ), psychological (e.g. women may be more able to detect sleep problems and more likely to attribute them to their drug use; Ogeil et al ., ) and sociocultural factors (e.g. a decreased likelihood of risk taking compared with men; Cherpitel, ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the use of stimulants such as caffeine is associated with almost double the likelihood of difficulty sleeping. 60,61 That is, similar to alcohol, there could be a bidirectional relationship between caffeine and sleep problems. 60 Furthermore, it is of note that because sleep deprivation can affect decision making, 47 the risk of work-related injuries may be elevated in this group.…”
Section: Discussionmentioning
confidence: 99%